Parental feeding perceptions and family health behaviours: an analysis based on nutrition and physical activity tendencies - Orhan, Bekir Erhan; Karaçam, Aydın; AlKasasbeh, Walaa Jumah; Amawi, Adam Tawfi; Canli, Umut (Frontiers in Pediatrics, 2026)
Childhood obesity is a growing public health concern with long-term physical and psychological consequences. Parents, as primary caregivers, play a central role in shaping children's eating habits and physical activity behaviours. This cross-sectional study examined how parental feeding perceptions and practices relate to family nutrition and physical activity patterns, and whether these associations vary according to parental demographic characteristics, particularly age. The sample comprised 268 parents of children aged 8–11 years in Türkiye, recruited from primary schools using purposive sampling. Data were collected via the Child Feeding Questionnaire (CFQ) and the Family Nutrition and Physical Activity Screening Tool (FNPA), both of which showed acceptable internal consistency in this sample. Pearson correlations, one-way ANOVA, and multiple linear regression with effect size estimates were used to analyse the data. Parental age showed no significant correlations with most CFQ subscales, except for a small negative association with restriction (r = –0.12, p < .05), indicating that older parents report slightly lower use of restrictive feeding practices. General obesity-related parental perceptions (perceived parent and child weight, concern about child's weight) were not significantly related to FNPA scores, and differences in CFQ and FNPA scores by parental gender, education level, and child age were statistically non-significant and negligible in magnitude. In contrast, FNPA scores were positively associated with parental responsibility (r = 0.32, p < .01) and monitoring (r = 0.41, p < .01). Regression analysis showed that higher responsibility and monitoring predicted more favourable family nutrition and physical activity patterns, whereas restriction was a negative predictor, with the model explaining approximately one quarter of the variance in FNPA scores. These findings underscore the importance of strengthening parental responsibility and monitoring, rather than restrictive feeding, in interventions designed to promote healthier lifestyle patterns in middle childhood.